(untitled) ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2024)
Background: Due to growth of classified Indian hotels, there is a need to assess the importance of ergonomics in such hotels and check their awareness amongst the stakeholders of Indian hospitality industry. Objective: Describing and highlighting different practices and means of ergonomics. Ascertaining the importance of ergonomics in core, and non- core areas of classified Indian hotels and hotel management institutes based on the opinions and empirical data, highlighting its effects on employee efficiency and revenue generation of a hotel including the phase of “New Normal” after the Covid- 19 pandemic. Methodology: Exploratory research design has been adopted where data has been collected via convenience sampling from Delhi NCR and Kolkata. Data has been collected from a sample of 100 individuals from employees and management of classified hotels and students and professors of hotel management institutes. Analysis was done with the use of MS Excel application. Perception has been recorded and studied. Results: As per the survey, majority, that is, 89% of the respondents agreed that ergonomics can increase the employee productivity and 91% acknowledged that ergonomics improve the revenue generation of hotels. Conclusion: Ergonomics is an irrefutable part of Indian classified hotels and steps need to be taken to improve the ergonomic standards.